PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) SEBAGAI VARIABEL INTERVENING PADA PDAM KABUPATEN KEDIRI - Mida Ainul Ghurroh; Syahirul Alim (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Human resource is important because it plays a significant role in an organization in order to achieve the organizational goals. Other than achieving the goals, human resource are also able to help determine goals that can be achieved through human resource owned by an organization or a company. Good management of the human resource is a must for a company if an organization wants to maintain its existence, develop, and compete with other organizations. Furthermore, good resource management will be able to increase the effectiveness and efficiency of the company in carrying out its functions. In the effort to improve the performance of the employee, there are numerous influencing factors, including Organizational Citizenship Behavior and organizational culture. This research was conducted in Tap-Water Company (PDAM) of Kediri Regency applying a quantitative method with a descriptive approach. The sample used in this study was 80 employees with a proportioned random sampling technique. Data were collected directly from respondents by using a data collection method in the form of a questionnaire. The data analysis used is path analysis. The results of the study showed that (1) Organizational Culture has a positive and significant influence on Organizational Citizenship Behavior, (2) Organizational Citizenship Behavior has a positive and significant influence on employee performance, (3) Organizational Culture has a positive and significant influence on employee performance. (4) Organizational Culture indirectly has a positive and significant effect on employee performance through Organizational Citizenship Behavior.